Copyright, creativity, big media and cultural value : incorporating the author - Bowrey, Kathy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"As the publishing, film and music industries are dominated by Big Media conglomerates, there is often recourse to simplistic ideological and conspiratorial readings of industry dynamics. Copyright, Creativity, Big Media & Cultural Value: Incorporating the Author explains why copyright is much more than a creator's private property right or a mechanism through which corporations control cultural production and influence mass consumption choices. The volume is grounded in extensive, painstakingly detailed and colourful original archival research into business histories of major successful artists including Conan Doyle, Hall Caine, Margaret Atwood, Dame Nellie Melba, Radiohead and Banksy, and the industries and genres that grew up around their activities. Chapters address big questions about how copyright generates income and how distributions of profits are allocated in the publishing, film and music industries. It includes discussion of the creation of new formats, the interplay between old media and new technologies, international copyright reform and cross-industry relations. Copyright, Creativity, Big Media & Cultural Value is a wide-ranging and important resource for students and practitioners of law and policy, media studies, cultural studies and literary history"--
What is the significance of authorship in copyright? -- Revisiting author theory in the domain of law -- A tale of three literary copyrights -- Imperial copyright and its costs -- Print capitalism meets Hollywood. The work of industrial authorship -- Why does a gramophone maker deserve a copyright? The role of celebrity, women and consumer markets in the recording industry -- Why Margaret Atwood, Radiohead, and Bansky are not anti-copyright.
OCLC-licensed vendor bibliographic record.
Keywords: Copyright; Authorship; Creative ability; LAW / Intellectual Property / Copyright; SOCIAL SCIENCE / Media Studies; LAW / Legal History